Evaluación docente para la mejora continua en el cantón Pujilí - Gualotuña Guiscasho, María Cristina (2017)
The present investigation is based mainly on the teacher evaluation as it is used to measure the knowledge and preparation of the educator, being that it should be focused on the professional and personal training, besides with the evaluation it will be possible to demonstrate the level of preparation to obtain an adequate Process of teaching learning, since an evaluation not only defines whether to approve or not but also gives us the guideline to establish a judgment on professional practice. In the educational institutions it was detected that the teacher is not preparing himself, but only as a mediator because he does not fully comply with his training as a teacher, which affects the students academically and especially in their professionalism, for this it is necessary to perform Course or trainings where it helps the teacher to train and self educate and at the same time help to arrive with a suitable PEA with the students. The application of surveys and direct observation to the students and teachers of the educational unit helped the analysis and interpretation of results. From the obtained diagnosis it was possible to conclude that it is necessary to evaluate the teacher so that it is updated according to the needs of the student, who at the same time fulfills the role of being the main axis for the formation of future generations.